African methods of music education: some reflections - Dargie, David (International Library of African Music, 1996)
The system of music education described above is based on a theory. Music theory - instrumental technique - performance of music -≫ reward for achievement = certificate: that is the theoretical design of the system. But there is a deeper theory behind it - a philosophical system, a way of thinking. We who have been educated in Western educational systems have grown so much into it that it seems our way of thinking is completely natural. It is the system of essentialism, of always trying to get at the essences of things. To do this, we abstract the qualities of the thing we wish to think about, often by constructing a definition of it. Having then made our definition, we have a look at the subject in the light of the definition -forgetting that it is we ourselves who have made the definition.
Keywords: African Music; Music Education